2014
DOI: 10.1021/jp4069703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxyl Group Substituted Spacer Group of Cationic Gemini Surfactants on Solvation Dynamics and Rotational Relaxation of Coumarin-480 in Aqueous Micelles

Abstract: The solvation dynamics and rotational relaxation of Coumarin 480 (C-480) have been investigated in the micelles of a series of gemini surfactants, 12-4(OH)n-12 (n = 0, 1, and 2), with increasing hydroxyl group substitution within the spacer group. Steady-state and time-correlated single photon counting (TCSPC) fluorescence spectroscopic techniques have been used to carry out such study. Steady-state and TCSPC fluorescence data support the location of probe molecule at the Stern layer. The solvation dynamics is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(115 citation statements)
references
References 71 publications
12
103
0
Order By: Relevance
“…Comparison of hydroxyalkylated geminis with conventional m-s-m analogs provide evidences that introducing hydroxyalkyl fragments markedly modifies functional activity (solubilization, catalytic, etc.) and physicochemical properties of systems (Fig.S1, Table 1) [12,27,33,64]. In particular, larger cmc decrease, lower isoelectric values, smaller aggregates with higher surface curvature and charge density, and more facile dehydration of polar groups occur in the case of hydroxyalkylated surfactants.…”
Section: Interaction Of Surfactants With Lipid Bilayermentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of hydroxyalkylated geminis with conventional m-s-m analogs provide evidences that introducing hydroxyalkyl fragments markedly modifies functional activity (solubilization, catalytic, etc.) and physicochemical properties of systems (Fig.S1, Table 1) [12,27,33,64]. In particular, larger cmc decrease, lower isoelectric values, smaller aggregates with higher surface curvature and charge density, and more facile dehydration of polar groups occur in the case of hydroxyalkylated surfactants.…”
Section: Interaction Of Surfactants With Lipid Bilayermentioning
confidence: 99%
“…While the role of the spacer architecture in the DNA-surfactant complexation is exemplified in literature [26][27][28][29], there is some disagreement in these data. Superior results were obtained for ethanediyl-and propanediyl versus the longer (-CH 2 -) 5 and (-CH 2 -) 12 polymethylene spacers in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12-4(OH)-12 gemini surfactant has a lower CMC than 12-4-12, as shown in Table 1. Saha et al [35,36] reported a decrease in the CMC of gemini surfactants with increasing hydroxyl group substitution on the spacer group. They rationalized this observation on the basis that the effect of increasing spacer chain length is dominant over the substituted hydroxyl group effect.…”
Section: Effect Of the Head Group Spacer And Chain Length On Cmcmentioning
confidence: 99%
“…The gemini surfactants, viz., C 16 -12-C 16 , 2Br -; C 16 -4-C 16 , 2Br -; C 12 -4-C 12 , 2Br -and C 12 -4(OH)-C 12 , 2Br -were synthesized following the same method as reported in the literature [33][34][35][36]. CDEEAB, CDMEAB and TDEEAB were obtained from Prof. R.M.…”
Section: Experimental Materialsmentioning
confidence: 99%